Oral lipoma: An uncommon clinical entity - Suresh K Sachdeva; Purnendu Rout; Sanjay Dutta; Pradhuman Verma (Wolters Kluwer Medknow Publications, 2013)
Lipoma is a benign mesenchymal tumor of mature fat cells. It is the most common mesenchymal tumor of the trunk and proximal portions of extremities. They account for the 0.5-5% of all benign tumors occurring in the oral cavity and hence presenting as an uncommon clinical entity intra-orally. In the oral cavity, they present as a slow growing, painless and asymptomatic yellowish sub-mucosal mass. Here is the case of a 45-year-old female, who presented with a growth in lower right buccal mucosal region. The purpose of this report is attempts to highlight the existence of this uncommon disease and to emphasis the need for dentists to be aware of frequency of occurrence of intraoral lipoma and hence that it is included in the differential diagnosis of oral soft tissue swellings.